2014
DOI: 10.1159/000365993
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Sorafenib in Intermediate-Stage Hepatocellular Carcinoma Patients Refractory to Transarterial Chemoembolization

Abstract: Objective: We compared the benefits of sorafenib therapy with continued transarterial chemoembolization (TACE) in TACE-refractory patients with intermediate-stage hepatocellular carcinoma (HCC). Methods: This retrospective study reviewed intermediate-stage HCC patients who underwent the first TACE. Patients were defined as TACE-refractory and divided into two cohorts: (1) patients who switched from TACE to sorafenib and (2) those who continued TACE. We evaluated the patient overall survival (OS) and time to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
169
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(183 citation statements)
references
References 21 publications
7
169
3
Order By: Relevance
“…Another possible reason is that post-cTACE treatment might have been effective, thereby contributing to the long OS observed in some cases with a short TTTP. For example, the use of sorafenib to treat patients with TACErefractory disease and a short TTTP actually prolongs OS [9,10] . However, in general we found that OS correlated with TTTP in patients with B1 or B2 substage HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible reason is that post-cTACE treatment might have been effective, thereby contributing to the long OS observed in some cases with a short TTTP. For example, the use of sorafenib to treat patients with TACErefractory disease and a short TTTP actually prolongs OS [9,10] . However, in general we found that OS correlated with TTTP in patients with B1 or B2 substage HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, sorafenib is the only treatment strategy available after failure of TACE [9,10] . However, in clinical practice, "progression" is not determined by development of a new small lesion, and switching from TACE to sorafenib or other therapies does not necessarily happen at this point.…”
Section: Introductionmentioning
confidence: 99%
“…In the SHARP trial sub-analyses [14], the hazard ratio of sorafenib against placebo was best in BCLC intermediate stage. When Ogasawara et al [18] and Arizumi et al [19] retrospectively compared two groups that satisfied the definition of TACE refractory, one group that continued with TACE and another group that changed to sorafenib, they reported that the sorafenib group had a significantly longer survival period. Therefore, we consider it important to understand the optimal timing for switching to sorafenib.…”
Section: Clinical Issues With Sorafenibmentioning
confidence: 99%
“…TACE is a palliative rather than curative treatment. It can be carried out repeatedly for unresectable HCC, but if the effect is judged to be poor, or TACE-refractory, introduction of sorafenib is considered (5,6). However, the safety and efficacy of early sorafenib induction after TACE has yet to be established.…”
Section: Introductionmentioning
confidence: 99%